PERAN BUDAYA ORGANISASI, KOMITMEN ORGANISASI, MOTIVASI KERJA DAN KEADILAN ORGANISASI TERHADAP KEPUASAN KERJA (The Role of Organizational Culture, Organizational Commitment, Work Motivation, and Organizational Justice towards Employee Job Satisfaction) - Kiki Fatmawati Samri Togala; Rahmat Madjid; Aidin Hudani Awasinombu (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2019)
The purpose of this study is to empirically examine and empirically explain the influence of organizational culture, organizational commitment, work motivation, and organizational justice on employee job satisfaction in the Department of Housing, Resettlement and Land Affairs of Kendari City. This research uses a quantitative approach with an associative explanatory design. Associative explanative research is research that aims to determine the effect of two independent variables on the dependent variable by examining the causal relationship between variables. The results showed that  (1) organizational culture, organizational commitment, work motivation and organizational justice had a positive and significant effect on employee job satisfaction, (2) organizational culture had a negative and not significant effect on employee job satisfaction. (3) Organizational commitment has a positive and significant effect on job satisfaction. (4) Work motivation has a positive and significant effect on job satisfaction. (5) Organizational justice has a positive and significant effect on job satisfaction at the Department of Housing, Settlement and Land Areas of Kendari City. Keywords: organizational culture, commitment, justice, and work motivation job satisfaction